Every dog has his day [large type] - McKinlay, Jenn (McKinlay, Jenn. Bluff Point romances., 2018)
"A stray kitten and a rambunctious poodle bring together a small-town bachelor and a single mother in the latest romance set in Bluff Point, Maine"--